2022
DOI: 10.1111/1756-185x.14358
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Turkish Version of the DASH‐TR Questionnaire in Rheumatoid Arthritis Patients, Based on Rasch Analysis

Abstract: Aim This study aimed to examine the validity and reliability of the Turkish version of the Disabilities of the Arm, Shoulder and Hand Problems (DASH‐TR) questionnaire in rheumatoid arthritis (RA) using the Rasch analysis. Method A total 97 individuals (13 men, 84 women; mean age:51.99 ± 11.12 years, range: 20‐65 years) diagnosed as having RA according to the criteria of the American College of Rheumatology were included. The functional status of the upper extremities was evaluated with the DASH‐TR questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…We knew that DASH was widely translated and cross-culturally adapted in many countries, considering it variably as a one-, two-, or three-factor instrument [ 69 73 ] in different clinical sample. Particularly, the Rasch analysis studies from Franchignoni et al [ 74 ] and Lehman et al [ 75 ] found three DASH factors, while Basakci et al [ 76 ] found two DASH factors, concluding that the DASH is not unidimensional. However, Wang et al [ 37 ] showed that one main factor explains 62% of the variance, stating that the structure of DASH can be considered as unidimensional, as confirmed also by the Rasch analysis by Van Lieshout et al [ 77 ] Hence, in literature, no consensus is available regarding the DASH factorial structure, as this psychometric property depends either on the clinical variables of the population studied either on the setting in which this instrument is administered.…”
Section: Discussionmentioning
confidence: 99%
“…We knew that DASH was widely translated and cross-culturally adapted in many countries, considering it variably as a one-, two-, or three-factor instrument [ 69 73 ] in different clinical sample. Particularly, the Rasch analysis studies from Franchignoni et al [ 74 ] and Lehman et al [ 75 ] found three DASH factors, while Basakci et al [ 76 ] found two DASH factors, concluding that the DASH is not unidimensional. However, Wang et al [ 37 ] showed that one main factor explains 62% of the variance, stating that the structure of DASH can be considered as unidimensional, as confirmed also by the Rasch analysis by Van Lieshout et al [ 77 ] Hence, in literature, no consensus is available regarding the DASH factorial structure, as this psychometric property depends either on the clinical variables of the population studied either on the setting in which this instrument is administered.…”
Section: Discussionmentioning
confidence: 99%
“…The Mayo Elbow Performance Score (MEPS), Disabilities of the Arm Shoulder and Hand (DASH), and Medical Research Council (MRC) scale and elbow exion power were used to evaluate the functional results. The operating surgeon performed clinical and radiological follow-ups [22][23][24].…”
Section: Patient Follow-upmentioning
confidence: 99%